2015
DOI: 10.1177/0004867415605171
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of psychiatric readmission among patients with bipolar disorder at an academic safety-net hospital

Abstract: Our study found enabling and need factors to be the strongest predictors of psychiatric readmission, suggesting that the prevention of psychiatric readmission for patients with bipolar disorder at safety-net hospitals may be best achieved by developing and implementing innovative transitional care initiatives that address the issues of multiple psychiatric hospitalizations, housing instability, insurance coverage and functional impairment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
33
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 49 publications
5
33
0
Order By: Relevance
“…Analysis of factors other than drugs of interest showed that the inpatient meta‐visit had an RR of 1.68 over the outpatient meta‐visit for psychiatric hospitalization ( P < 2.23 × 10 −308 ), supporting the evidence that previous hospitalization is a strong predictor of subsequent hospital admission in patients with BD . Consistent with our data, baseline substance use disorder, psychosis, and use of anticonvulsants and anxiolytics were previously reported to be risk factors for hospitalization in BD .…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Analysis of factors other than drugs of interest showed that the inpatient meta‐visit had an RR of 1.68 over the outpatient meta‐visit for psychiatric hospitalization ( P < 2.23 × 10 −308 ), supporting the evidence that previous hospitalization is a strong predictor of subsequent hospital admission in patients with BD . Consistent with our data, baseline substance use disorder, psychosis, and use of anticonvulsants and anxiolytics were previously reported to be risk factors for hospitalization in BD .…”
Section: Discussionsupporting
confidence: 88%
“…Analysis of factors other than drugs of interest showed that the inpatient meta-visit had an RR of 1.68 over the outpatient metavisit for psychiatric hospitalization (P < 2.23 × 10 −308 ), supporting the evidence that previous hospitalization is a strong predictor of subsequent hospital admission in patients with BD. [29][30][31][32][33] Consistent with our data, baseline substance use disorder, psychosis, and use of anticonvulsants and anxiolytics were previously reported to be risk factors for hospitalization in BD. 30 The findings on the reduced risk of psychiatric hospitalizations for patients on antibiotics and non-steroidal anti-inflammatory drugs contribute to the evidence suggesting the importance of immune alterations, inflammation, and the microbiome in BDs.…”
Section: × 10 −12supporting
confidence: 90%
“…Kraepelin reported that the recurrence of episodes tended to accelerate over time, which leads to shortening of inter‐episodic intervals . In this same vein, some studies using the nationwide registration of all psychiatric hospitalizations from Denmark and others showed that the rate of relapse leading to hospitalization increased with the number of previous episodes . However, it has been argued that some of these studies, and also Kraeplin's observations, may be due to a computational artifact .…”
Section: Resultsmentioning
confidence: 99%
“…31 The length of stay of the patient was not found to be significant in this study, even though some studies have showed that a shorter length of stay during the index hospital admission led to a higher risk of readmission. 3,41,45 This has become an important finding as many countries have pressed for a shorter length of stay and some psychiatrists may discharge a patient prematurely before recovery in an attempt to hasten the patient's reintegration into society in the community. 46 This may be because of the relatively long length of stay of patients in Hong Kong compared with other countries, with less pressure for early discharge, and data being partly skewed by the discharge episodes of certain patients who have lived in psychiatric institutions for years.…”
Section: Main Findingsmentioning
confidence: 99%